Effect of onychomycosis on pulse oximeter - Nazik, Hulya; Nazik, Selcuk; Gul, Feride C.; Demir, Betul; Mulayim, Mehmet K. (Wolters Kluwer Medknow Publications, 2018)
Objective Onychomycosis causes nail thickness and discoloration of the dorsum of the nail plate. This study was aimed to investigate the effect of discoloration and nail thickness associated with onychomycosis on pulse oximetry measurement. Materials and methods The involvement degree of onychomycosis was determined using onychomycosis severity index (OSI). Two different measurements were recorded by pulse oximetry. The first one was from the nail with onychomycosis, and the second one was from the normal nail of the same hand. Results A total of 93 onychomycosis cases were included in the study. When SpO2 values of white nail color were measured, it was statistically significant higher in the onychomycosis group than the control (P<0.001). On the contrary, in the yellow nail, SpO2 values were lower in the onychomycosis group (P<0.001). Similarly in the brown nail, SpO2 values were lower in the onychomycosis group, but there was no statistically significance (P=0.083). It was determined that there was no statistically significant difference between SpO2 values and OSI (P=0.563). Conclusion As a result, SpO2 values were affected by discoloration owing to onychomycosis. SpO2 values were found lower in patients with moderate and severe OSI, which is related to nail thickness than the control. It was concluded that the discoloration and nail thickness associated with onychomycosis were effective on pulse oximetry measurement.
Keywords: discoloration; nail thickness; onychomycosis; pulse oximetry